Reverse redistribution on Rb-82: Does the mechanism of stress play a role? - Martineau, Patrick; Harel, Francois; Pelletier-Galarneau, Matthieu (World Journal of Nuclear Medicine, 2019)
We present a case of reverse redistribution in a patient imaged with Rb-82 positron-emitting tomography. The patient was imaged twice in rapid succession using pharmacological stress – once with dipyridamole and once with dobutamine. The patient demonstrated reverse redistribution after dipyridamole but not after dobutamine administration. We speculate on the relationship between the pharmacological stressing agent and the presence of reverse redistribution.
Keywords: Myocardial perfusion imaging; positron-emitting tomography; Rb-82; reverse redistribution